2015
DOI: 10.1002/ehf2.12042
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of supramaximal titrated inhibition of renin‐angiotensin‐aldosterone system in idiopathic dilated cardiomyopathy

Abstract: AimsThe optimal dosing strategies for blocking the renin‐angiotensin‐aldosterone system in idiopathic dilated cardiomyopathy (IDCM) are poorly known. We sought to determine the long‐term efficacy and safety of supramaximal titration of benazepril and valsartan in patients with IDCM.Methods and results480 patients with IDCM in New York Heart Association functional class II–IV and with left ventricular ejection fraction ≤35% were randomly assigned to extended‐release metoprolol (mean 152 mg/day, range 23.75–190)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The use of MitraClip procedure was associated with a significantly lower risk of reoperation compared to the use of GDMT alone at a mean follow-up of 15.8 months. The clinical benefit associated with the use of MitraClip procedure is by pathoanatomical and pharmacological means as it was more evident in correcting geometric changes of mitral valve than medical treatment alone including renin-angiotensin system inhibitors [21][22][23][24][25][26][27][28] and beta-adrenergic blockade [29][30][31][32][33][34][35] on reducing mitral regurgitation. These medications work by attenuating LV remodeling in chronic severe MR [36,37] often in association with temporary use of diuretics [38].…”
Section: The Percutaneous Approachmentioning
confidence: 99%
“…The use of MitraClip procedure was associated with a significantly lower risk of reoperation compared to the use of GDMT alone at a mean follow-up of 15.8 months. The clinical benefit associated with the use of MitraClip procedure is by pathoanatomical and pharmacological means as it was more evident in correcting geometric changes of mitral valve than medical treatment alone including renin-angiotensin system inhibitors [21][22][23][24][25][26][27][28] and beta-adrenergic blockade [29][30][31][32][33][34][35] on reducing mitral regurgitation. These medications work by attenuating LV remodeling in chronic severe MR [36,37] often in association with temporary use of diuretics [38].…”
Section: The Percutaneous Approachmentioning
confidence: 99%
“…Inhibition of the renin–angiotensin–aldosterone system remains the mainstay of therapy in patients with chronic HF. He et al performed a randomized trial to assess the efficacy and safety of supramaximal titrated inhibition in patients with idiopathic dilated cardiomyopathy. They concluded that even supramaximal doses of benazepril and valsartan were tolerated and produced extra benefit on top of their low‐dose counterparts with regard to clinical outcome and cardiac reverse remodelling .…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…As described earlier, an ACE inhibitor, lisinopril, or an ARB, losartan, at high dose produced better clinical outcomes in patients with HF compared with each at low dose but did not decrease mortality significantly. 5,6 On the other hand, He et al reports that supramaximal dose of benazepril or valsartan improves not only cardiac function but also survival in patients with DCM compared with the low dose of each medication, 16 which indicates that ACE inhibitors or ARBs at supramaximal-dose might produce better outcomes in patients with EF compared with those at high dose (target dose). These unique findings are derived from a single-centre prospective, randomized, and controlled trial.…”
Section: Angiotensin Receptor Blocker For the Treatment Of Heart Failurementioning
confidence: 99%